Het plan voor katholiek Amsterdam 1969: Cityvorming, kerk en de rol van de sociale wetenschappen in het beleid - Sengers, Erik (Religie & Samenleving, 2015)
The importance of social sciences for church policy is the reason for a fierce debate in this journal. In the case of the Dutch Roman Catholic Church, the conflictuous events of its history are considered in the discussion. This paper shows that it is more fruitful to investigate small-scale case studies to establish the role of social sciences in church policy. Here, the Pastoral Plan for the inner city of Amsterdam (1969) is presented as an example. The plan foresaw the closure and re-functionalization of many churches because of the expected restructuring of the inner city of Amsterdam. As this restructuring did not take place as expected, the whole plan soon became superfluous. The role of social sciences in this Plan is clear at every possible level, but the concrete influence has to be established by more, and ecumenical, case studies.